2017
DOI: 10.1515/pjct-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of paint matrix composition and thickness of paint layer on the activity of photocatalytic paints

Abstract: Silicate, acrylic and latex photocatalytic paints were analyzed in regards to impact of paint matrix composition and paint layer's thickness on performance in two photocatalytic tests. These included performances in photocatalytic decomposition of benzo[a]pyrene (BaP) and assessment of photocatalytic activity through use of smart ink test. Silicate photocatalytic paints displayed lower photocatalytic activity in comparison to acrylic and latex photocatalytic paints in both tests, despite the similar content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…To have a preliminary estimation, in our case, the ultraviolet lamp, employed in the photocatalytic tests, maximum interact with some hundreds of micrometres [19]. This value agrees with literature data in which it was found that more porous structure of paint layer results in deeper penetration of ultraviolet radiation [20]. This means that the photocatalytic tests, conducted according to established procedures [21], give reliable results in terms of photodegradation of the dye used to simulate the dirt.…”
Section: Resultssupporting
confidence: 85%
“…To have a preliminary estimation, in our case, the ultraviolet lamp, employed in the photocatalytic tests, maximum interact with some hundreds of micrometres [19]. This value agrees with literature data in which it was found that more porous structure of paint layer results in deeper penetration of ultraviolet radiation [20]. This means that the photocatalytic tests, conducted according to established procedures [21], give reliable results in terms of photodegradation of the dye used to simulate the dirt.…”
Section: Resultssupporting
confidence: 85%
“…Various derivatives of this polycyclic aromatic hydrocarbon have displayed strong and distinct excimer emission with high fluorescence quantum yield. Though the fluorophore occasionally experiences quenching due to aggregation in solid or concentrated form, pyrene derivatives are used extensively in fluorescent probes, food colorants, OLEDs, biosensors, biomarkers, corrosion inhibitors, printing inks, chemosensors, colorimetric sensors (Kathiravan et al 2014;Domeño et al 2017;Shen et al 2019;Srinivasan et al 2021;Wang 2021), electroluminescent devices, paints, optoelectronics, (Gowri et al 2020;Jeyasingh et al 2021;Kr et al 2021;Uzun 2021;Yao et al 2021), and anti-counterfeiting (Maeda et al 2001;Homa et al 2017;Mohamed et al 2020;Boonnab et al 2021). Although various colorants are available, very few inks, such as bio-ink and tattoo inks, have been developed utilizing pyrene, primarily for inkjet and 3D printing.…”
Section: Introductionmentioning
confidence: 99%